Beyond EGFR and ALK inhibition: Unravelling and exploiting novel genetic alterations in advanced non small-cell lung cancer. Issue 5 (May 2015) - Califano, Raffaele; Abidin, Aidalena; Tariq, Noor-ul-Ain; Economopoulou, Panagiota; Metro, Giulio; Mountzios, Giannis
Highlights Novel molecular events that characterize NSCLC transformation may represent oncogenic drivers amenable to targeted therapy. Drivers beyond EGFR and ALK inhibition have emerged as novel molecular targets with potential therapeutic implications. These targets include genetic alterations in the genes KRAS, BRAF, HER2, PI3KCA, DDR2, ROS1, RET, MET, HER2 and FGFR1. A number of molecules that target the aforementioned genetic alterations are in early phase of clinical development.